Formulation and Characterization of Fast Disintegrating tablets of Amlodipine using Super-disintegrants - Behin Sundara Raj, Punitha I.S.R., Suraj Dube (Journal of Applied Pharmaceutical Science)
Amlodipine besylate is a long-acting calcium channel blocker used to treat chronic stable angina, vasospastic angina and hypertension. Amlodipine is a sparingly soluble orally administered drug and the rate of absorption is often controlled by the rate of dissolution. The rate of dissolution will increase by incorporating the drug in a fast dissolving dosage form. An attempt will be made to develop rapidly disintegrating oral tablets of Amlodipine Besylate by direct compression method. In this study, Fast Dissolving Tablet (FDT) was prepared using direct compression method using Crospovidone and Sodium starch glycolate as the super disintegrants. Amongst all formulations, formulation F3 prepared by a combination of both Crospovidone and Sodium starch glycolate showed least disintegrating time, and faster dissolution of 87%. Combination of super disintegrants were found to be better to formulate fast dissolving tablets of Amlodipine besylate.
Keywords: Fast Disintegrating tablet,Crospovidone,Sodium starch glycolate,Amlodipine Besylate.